Avaliação de aprendizagem na escola plural: o que ocorre na prática? - Jose Luiz Saldanha da Fonseca (2003)
This research work had a main purpose to find answers to the question: What are the conceptions (beliefs, opinions, attitudes) of science teachers from two municipal schools from Belo Horizonte who have implanted the pedagogic project Escola Plural and of their students about the learning evaluation proposed by this project and what kind of evaluation practices are the teachers using? The research has been done using observation, interviews, focus groups, questionnaires and dossier analysis. As a result of the work, answer to the question placed in the title, I can assert that the practices on learning evaluation in the two schools are not yet the proposal of the project Escola Plural but nor are they the traditional learning evaluation which the new proposal intends to change. The emergency of the new logic of evaluation observed in the practices of the teachers coexists with the more traditional logic, still deep-rooted in the conceptions of the teachers researched and of their students, which is manifested in the interviews and focus groups.